O desenvolvimento profissional de professores das séries iniciais do ensino fundamental - Chakur, Cilene Ribeiro De Sá Leite [UNESP] (Universidade de São Paulo, Faculdade de Filosofia Ciências e Letras de Ribeirão Preto, Programa de Pós-Graduação em Psicologia, 2005)
A previous research showed that the professionality of teacher's from 5th to 8th grades is developed in different levels and that there are certain patterns in the teachers' reactions up against daily school conflicts. This present study intended to verify if there would be differences in the professionality levels between the teachers. Fourteen teachers from 1st to 4th grades of a public school in a city from São Paulo State were interviewed about hypothetical stories, each one containing a problem to be judged/solved; the analysis complied with piagetian criteria. The results indicated that these teachers' depositions are distributed by the same levels previously found and the reaction ways to the conflict are just the same. It was conclude that the teacher's professional development occurs in a sequence of hierarchical levels and in order to make the professional schemes progress and improve it is fundamental to be aware of the presented obstacles, first step for its solution.

Pesquisa anterior mostrou que a profissionalidade de professores de 5ª a 8ª séries se desenvolve em diferentes níveis e que há certos padrões nas reações dos professores diante de conflitos do cotidiano escolar. O presente estudo investigou se existiriam diferenças entre professores quanto aos níveis alcançados. Foram entrevistadas 14 professoras de 1ª a 4ª de uma escola pública paulista sobre histórias hipotéticas, cada qual contendo problema a ser julgado/solucionado; a análise obedeceu a critérios baseados no referencial piagetiano. Os resultados indicaram que os depoimentos dos professores de 1ª a 4ª séries se distribuem pelos mesmos níveis encontrados anteriormente e que são as mesmas as formas de reação ao conflito. Conclui-se que o desenvolvimento profissional docente ocorre em uma seqüência de níveis hierárquicos e, para que os esquemas profissionais progridam e se aperfeiçoem, é fundamental a tomada de consciência dos obstáculos enfrentados, primeiro passo para a sua solução.
The professional development of teachers from the initial grades of primary school
Keywords: teacher's professionality; teacher's professional development; acquisition levels of the teacher's professionality; profissionalidade docente; desenvolvimento profissional do professor; níveis de aquisição da profissionalidade docente